THEMATIC ANALYSIS ON TAKHARRUJ DIVISION IN ISLAMIC INHERITANCE ESTATE DISTRIBUTION - Noratiqah Ramli; Noramyfatin Kamaruzzaman; Noraziah Abd Rashid; Norhaifa Ganti; Mohd Khairy Kamarudin; Norakmal Mardhiah Aimi Mizan (Journal of Islamic, Social, Economics and Development, 2021)
Takharruj division is one of the methods for inheritance estate division among Muslim heirs. This type of division could facilitate the process of inheritance estate management which is a major problem for Muslims in Malaysia. Therefore, this study aimed to identify the factors that inspire the heirs to succeed inheritance estate via takharruj division based on authority perception and experience. Semi-structured interview was conducted among officers at Small Estate Division Unit. Thematic analysis was employed to determine potential factors of takharruj for inheritance estate distribution. The result highlight that the foremost reasons of takharruj division being chosen as the inheritance estate division were relationship among the heirs and the position of inheritance estate. Relationship among heirs can be defined as siblings’ affection, strengthening relationship’ and needs of other heirs. Whereas position of inheritance estate referred to land scarcity and multiple ownership. Thus, it was suggested that policy makers should formulate specific guidelines related to inheritance estate management which could assist the heirs to manage the estate effortlessly and effectively.